Factors Associated With Coverage of Health Insurance Among Women in Malawi - Chauluka, Margaret; Uzochukwu, Benjamin S. C.; Chinkhumba, Jobiba (Frontiers in Health Services, 2022)
Introduction: Access to health care for vulnerable groups including women has long been a theme encouraged worldwide from the first general assembly on health to the current sustainable development goals. Despite many countries having a free public health care system, there are inequalities in access to care and significant out-of-pocket spending, pushing most women into poverty against the principles of universal health coverage.. Coverage of Malawian women with health insurance is poor thus there is limited cushioning and high risk of poverty as women bear costs of care as primary caregivers. There is need to explore determinants of coverage of health insurance among women in Malawi to inform health policy. Methodology: This study was quantitative in nature, using cross sectional secondary data from the 2015-2016 Malawi Demographic Health Survey involving women aged between 15 years to 49 years. We assessed factors associated with insurance coverage by comparing women with and without insurance schemes using binary logistic regression. Analysis was done using STATA statistical package version 13. Results: The analysis included a total of 24,562 women with a mean age of 28 SD (9.3). Of these cases, 1.5% had health insurance. High education attainment, occupation and wealth were significantly associated with health insurance ownership, with all having p values of <0.01. On the other hand a womans residence, marital status and who heads a household were not associated with ownership of health insurance significantly. Conclusion: Education, occupation, wealth have a key role in influencing a woman’s choice in owning health insurance. This informs policy makers and health insurance providers on how best to approach women’s health financing and factors to target in social security programs and health insurance products that speak to women’s needs and capacity.